Nitric oxide conversion to nitrogen on the W3O6 cluster through the ammonia selective catalytic reduction reaction: a DFT study - Hafiz Aji Aziz; Rathawat Daengngern (Results in Chemistry, 2026)
Nitric oxide (NO), a harmful byproduct of fossil fuel combustion, can be effectively removed via the Selective Catalytic Reduction (SCR) process using ammonia (NH 3 ), producing N 2 and H 2 O. This study investigates the SCR mechanism of NO by NH 3 over the W 3 O 6 cluster using the DFT/M06-L/LANL2DZ-ECP/aug-cc-pVTZ method. Chemisorption of NO on W 3 O 6 forms a stable W 3 O 6 –NO intermediate (−34.47 kcal·mol −1 ), initiating the reaction, followed by NH 3 adsorption (−25.14 kcal·mol −1 ). The overall mechanism includes: (i) NH 3 adsorption and dehydrogenation, (ii) NO adsorption and nitrosamine formation, (iii) nitrosamine rearrangement, (iv) N 2 and H 2 O formation, and (v) gas desorption and catalyst regeneration. Nitrosamine formation is identified as the rate-determining step, with an activation barrier of 33.45 kcal·mol −1 . The calculated rate constant (1.88 × 10 −12 s −1 ) from Harmonic Transition State Theory (HTST) confirms its critical role in controlling the SCR reaction kinetics.
Keywords: Ammonia Synthesis and Nitrogen Reduction; Inorganic Chemistry and Materials; Nanomaterials for catalytic reactions